Successful Postnatal Management of Ruptured Giant Sacrococcygeal Teratoma - Al ani, Muataz Abdulhameed (Journal of Neonatal Surgery, 2017)
Most sacrococcygeal teratomas present between the 22nd and the 34th week of gestation. The diagnosis of sacrococcygeal teratoma on routine antenatal sonograms is associated with a greater than expected incidence of prenatal and perinatal complications. We report a premature baby with intrauterine spontaneous rupture of giant sacrococcygeal teratoma which was managed successfully.